The effectiveness of bright light exposure in shift-worker nurses: A systematic review and meta-analysis - Seyedeh Zahra Aemmi; Eesa Mohammadi; Hamid Heidarian-Miri; Malek Fereidooni-Moghadam; Hatam Boostani; Kourosh Zarea (Sleep Science, 2020)
Bright light exposure is as one of the non-pharmacological measures to sleep management in shift-worker. This study was conducted to determine the effectiveness of bright light exposure in shift-worker nurses. We performed a systematic review and meta-analysis according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement and using existing literature in the following databases: Cochrane Library, Embase, PubMed, Scopus, Web of Science, to examine any eligible and relevant interventional (randomized controlled trial, experimental and quasi-experimental studies) which were published by December 31, 2018. The obtained documents were analyzed using Stata 14.1 and Cochrane Collaboration’s RevMan 5.3. Five studies met eligibility criteria. Results from fixed-effect meta-analysis of the included studies revealed that the exposure could decrease the sleepiness levels, complaints related to shift-work, insomnia and increased the psychomotor error (95% confidence interval (CI): -0.87,-0.43, p=0.000, I2=98.6%), alertness and daytime sleep duration following night shifts (95% CI: 0.08,0.99, p=0.000, I2=92.7%). However, in the random effects model, none of them were statistically significant. Although the results of fixed-effect are in favor of beneficial effects of bright light exposure in shift-worker nurses, the random effects could not approve these findings. Maybe because of either large heterogeneity or insufficiency of the number of studies. Besides, because of the low number of studies, it was impossible to deal with high amount of heterogeneity using subgroup analysis or meta-regression. So the controversy on this topic continues to persist, which highlights the need for more welldesigned randomized control trials with larger sample sizes in the future.